Sistem Pendukung Keputusan Gerai Di Pusat Perbelanjaan Modern Provinsi Bali: Metode ANP - Andien Rachma Fadillah; I Komang Ari Mogi; Cokorda Rai Adi Pramartha; I Gusti Ngurah Anom Cahyadi Putra (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2024)
The rapid competition in the business world due to the Era of Revolution 4.0 has resulted in the need for the business world to maintain competitiveness in front of consumers. Expanding the market by establishing a presence in easily accessible locations such as modern shopping centers is one way to achieve this. Choosing the best location among the many modern shopping centers in Bali for opening an outlet is a challenge for business people, who in this research only used case studies in Bali Province of 16 Modern Shopping Centers. The aim of this research is to develop a web-based decision support system to facilitate the location selection process for business actors. This research will utilize the Analytic Network Process (ANP) method for decision making regarding outlet selection in modern shopping centers. The development of a web-based decision support system enables businesses to effectively select the most suitable locations within modern shopping centers to open new outlets, thereby maximizing their market presence. This system will help businesses make decisions on selecting locations for modern shopping centers in Bali Province.